Zhao Xiaosheng and his original piano solo works / Xue Ke - Xue , Ke (2020)
As an influential composer in contemporary Chinese piano development, Zhao Xiaosheng has made outstanding contributions through his piano compositions, including original piano solos, transcriptions, etudes, concertos, and impromptus. His six original piano solos illustrate the development of his compositional career, which coincided with the development of Chinese new music from the period of the Cultural Revolution to the Reform and Opening-up. Therefore, in the context of Chinese new music, this research attempts to study Zhao Xiaosheng’s contributions by looking into his six original piano solo works, namely Textile Worker (纺织工人) (1974), Fisherman’s Song (渔歌) (1975), Ballade in D♭ Major (D♭大调叙事曲) (1976), Ballade in D Gong Mode (D宫调叙事曲) (1976), Hegemon-King Removes His Armor (霸王卸甲) (1981), and Tai Chi (太极) (1987). The current study found that past literature mainly focused on the analyses and evaluations of Zhao’s Tai Chi Composition System and piano solo Tai Chi, and rarely examined his other five solo works. In addition, there is a lack of in-depth analysis of Tai Chi in terms of its organization of pitch-class sets and performance practice. Therefore, the research gaps found in the past literature became the focus of this study, and a discussion of the relationship between Zhao’s piano solos and Chinese new music is also carried out. A qualitative inquiry into the study of Zhao Xiaosheng’s original piano solo works attempts to answer the research objectives by performing text analysis of his six piano solo works, interpretations of the piano solo pieces in the area of performance practice, and identification of the compositional characters in the context of Chinese new music. Methods such as semi-structured interview with the composer, literature review, and score and recording analysis were employed to obtain primary and secondary data. A triangulation that allowed data validation as necessity of trustworthiness was the premise of acquiring a reasonable and valuable analysis result in portraying Zhao’s works. By analyzing the six original piano solo works, the outcome revealed that Zhao’s piano solos mirrored the Chinese political and musical situation of the 1970s and 1980s, during which his pursuit of establishing Chinese musical language and form was reflected in the soundscape, context, content, rhyme, and aesthetics of his works. An integration of two-pole cultural absorption—the inheritance from China and learning from the West—is shown in the following pairs of relationships: program and non-program, sinicization and globalization, as well as Chinese identity and Western music education background.